PERAN INFLAMASI DAN AMILOIDBETA PADA PATOLOGI PENYAKIT ALZHEIMER - Jan S. Purba* (NEURONA, 2011)
WORLDWIDE PREVALENCE OF ALZHEIMERS DISEASE AD IN YEAR 2006 WAS ESTIMATED TO BE 266 MILLION AND BY 2050 IS EXPECTED TO QUADRUPLE BECAUSE OF THE INCREASING LIFE EXPECTANCY IN MANY COUNTRIES THE MAIN CAUSE OF AD IS GENERALLY ATTRIBUTED TO INCREASED PRODUCTION AND ACCUMULATION OF AMYLOIDBETA A IN ASSOCIATION WITH NEUROFIBRILLARY TANGLES NFT FORMATION AND SYNAPTIC DEGENERATION